1999
DOI: 10.1097/00000478-199901000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Lymphoid Hyperplasia and Cutaneous Marginal Zone Lymphoma

Abstract: Cutaneous marginal zone lymphoma (MZL) is a recently described low-grade B-cell lymphoma that usually follows an indolent course. This tumor shares many histologic and clinical features with cutaneous lymphoid hyperplasia (CLH), a benign reactive lymphoid proliferation. Sixteen biopsy specimens from 14 patients with CLH were studied, and compared with 16 cases of cutaneous MZL (9 primary cutaneous, 7 with secondary involvement of the skin) to determine whether there were features that would permit their distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 25 publications
3
85
4
1
Order By: Relevance
“…It is usually localized and well demarcated from surrounding tissue [1] . Pseudolymphoma may occur at numerous sites including the stomach [7] , lung [8] , ocular adnexa [9] , hard palate and oral mucosa [10] , skin [11] , and breast [12] . To the best of our knowledge, 32 cases (including ours) of hepatic pseudolymphoma have been reported in the English and Japanese literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually localized and well demarcated from surrounding tissue [1] . Pseudolymphoma may occur at numerous sites including the stomach [7] , lung [8] , ocular adnexa [9] , hard palate and oral mucosa [10] , skin [11] , and breast [12] . To the best of our knowledge, 32 cases (including ours) of hepatic pseudolymphoma have been reported in the English and Japanese literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…All seven reported cases of breast pseudolymphoma were female [12] , but breast examination is limited almost exclusively to females, which could bias these findings. Reported male-female ratios of pseudolymphoma of the hard palate and oral mucosa [10] , lung [8] , and skin [11] were 1:2.8, 1:1.2 and 1:1.8, respectively, while ocular adnexal lymphoid hyperplasia affects men and women about equally [9] . Thus the extreme female asymmetry of hepatic pseudolymphoma is a unique characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Although these conditions were formerly known as lymphadenosis benigna cutis, including synonyms such as lymphocytoma cutis, pseudolymphoma of Spiegler-Fendt or cutaneous lymphoplasia, and lymphocytic infiltration of Jessner, the term cutaneous lymphoid hyperplasia (CLH) is currently the recommended term [1,2]. In particular, there are various opinions about whether lymphocytic infiltration of Jessner is a distinct entity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that lesions that are really cutaneous marginal zone lymphoma (CMZL) may have been erroneously diagnosed as CLH [1,2,5]. Both CMZL and cutaneous follicular lymphoma are uncommon in the Japanese population [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, this finding was almost absent in Germany and the United States cases. Tissue eosinophilia has been reported in 4 of 15 American cases, 23 although the degree of eosinophilia was not specified. In malignant lymphoma, tissue eosinophilia is often associated in Hodgkin's lymphoma and T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%